Reduced risk of breast cancer associated with recreational physical activity varies by HER2 status. (27th April 2015) - Ma, Huiyan; Xu, Xinxin; Ursin, Giske; Simon, Michael S.; Marchbanks, Polly A.; Malone, Kathleen E.; Lu, Yani; McDonald, Jill A.; Folger, Suzanne G.; Weiss, Linda K.; Sullivan‐Halley, Jane; Deapen, Dennis M.; et al.
<x xml:space="preserve">Abstract</x> It remains unclear whether physical activity protects against all or only specific subtypes of breast cancer defined by the status of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), or p53. In this study, the protective effect varies by HER2 status, but not other tumor markers. These findings suggest that HER2 may play an important role in biological mechanisms through which physical activity decreases the risk of developing breast cancer. <boxed-text content-type="graphic" id="cam4465-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>